Cytomegalovirus disease in patients with hematopoietic stem cell transplantation, experience over 8 years - Laura Diaz; Joaquin Rosales; Fernando Rosso; Maria Rosales; Mayra Estacio; Eliana Manzi; Francisco Javier Jaramillo (Hematology, Transfusion and Cell Therapy, 2020)
Objective: Cytomegalovirus infection and disease are significant causes of morbidity and mortality among patients with hematopoietic stem cell transplantation. The aim of this study was to assess the frequency of cytomegalovirus infection and characterize the patients who developed the disease. Methods: A retrospective cohort study was performed among adult patients, recipients of allogeneic HSTC between 2008 and 2015. Taking into account the institutional protocol of prophylaxis infections in hematopoietic stem cell transplantation, patients received either preemptive therapy or prophylaxis with valganciclovir. Infection was defined as a positive pp65 antigenemia assay or PCR higher than 500 copies/mL. Disease was defined as viremia with evidence of end organ damage. Results: Seventy patients were included, the median age was 36 years old (IQR 17–62). A total of 93% of the recipients had a positive serology. The Cytomegalovirus infection occurred in 59% of the patients. Eleven patients developed disease (16%), the most frequent manifestation being colitis, followed by pneumonitis and a single case of retinitis. There were no differences between the preemptive therapy or prophylaxis groups. The mean time of onset of the disease was day 94 post-transplant. Three patients developed disease with a viral load lower than 1000 copies/mL. Conclusion: The incidence of cytomegalovirus infection after transplantation at our institution is high. It was found that the disease can occur with any level of viral load and is associated with high mortality. Keywords: Cytomegalovirus infection, Hematopoietic stem cell transplantation, Viral load